Twentieth-century economics - Samuels, Warren S. (Emerald, 2000)
The archival collection has two parts. The first presents correspondence between the American economist, Alfred S. Eichner, and the English economist, Joan Robinson, and related documents. The correspondents were major contributors to Post Keynesian economics in terms of both ideas and creating self-consciousness. The second presents hitherto unpublished correspondence and documents pertaining to the nature, rise and limits of quantitative methodology in economics. The materials are from Wesley C. Mitchell, Henry Schultz, and Arthur F. Burns. They examine many issues that remain in contention today.
Keywords: Business & Economics -- Economic History.; Business & Economics -- Economics -- General.; Economics.; USA.; elektronické knihy; electronic books